Growth and Bio-Pigment Production of Three Microalgal Species in Organic and Inorganic Media and Determination of Generation Time – A Comparative Study - Murugan, T. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Microalgae has been used as food for centuries by different populations and only rediscovered in recent years. Phycocyanin is a water soluble blue pigment that gives Spirulina its bluish tint. It is widely found in Blue green algae like Spirulina. Phycocyanin is a powerful water soluble antioxidant, scientists in Spain showed that an extract of Spirulina containing phycocyanin is a potent free radical scavenger and inhibits microsomal lipid peroxidation. This present study was aimed to evaluate the growth of three micro algal species (blue green algae- Spirulina platensis, Spirulina platensis var lonar and the green alga- Chlorella sp.) on organic media. The organic media were formulated from Spent Wash (SW) and Swine Dung (SD). The inorganic media (Zarrouk’s medium for Spirulina and Sarokin & Krauss medium for Chlorella) were used as control (C). The biomass yields of all the three algae were recorded. In addition, the C-phycocyanin yield of the two species of Spirulina also compared to the control medium. The cultivation was carried out for a period of 15 days, at 27C and at constant light intensity of 1.7 klux. The physico-chemical characteristics of both organic media were analyzed. Sizeable reduction in hardness, calcium and chloride content were observed in the media, after cultivation of the microalgae. The generation time of three micro algae in organic and inorganic media were also calculated. Overall, Spent wash (SW) showed better prospects than the control in terms of both biomass and C-phycocyanin production.